PEMANFAATAN “ALID" (ALAT EVALUASI DIGITAL) DENGAN MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V DALAM PEMBELAJARAN PENDIDIKAN PANCASILA SDN PUNTEN 01 - Zalfa Ramadhania Lafitra; Arina Restian; Nur Suhartanti (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The digital era has changed the face of education, making technology an inseparable component in the learning process. However, in the context of teaching Pancasila in the classroom, conventional methods still dominate, with minimal use of technology. As a result, student participation tends to be passive, interest in learning decreases, and academic achievement is not optimal. This research aims to improve the academic performance of class V students at SDN Punten 01 in the Pancasila subject. The method used is the application of the Problem-Based Learning (PBL) model which is integrated with "Alid" (digital assessment tool). Adopting a Classroom Action Research (PTK) format, this study implemented four stages: planning, implementation, observation, and reflection. A total of 21 fifth grade students were involved as research subjects. Data was collected through tests and analyzed using qualitative and quantitative approaches. The results of the research show the effectiveness of the combination of the PBL model and digital assessment tools in improving the Pancasila learning outcomes of fifth grade students at SDN Punten 01. There was a significant increase from the average score in the pre-test cycle I of 58.09 to 84.28 in the post-test cycle II , indicating a substantial increase in learning activity.